2002
DOI: 10.1074/jbc.m204052200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Phosphagen Kinase Systems Confers Resistance to Transient Stresses in Saccharomyces cerevisiae by Buffering the ATP Pool

Abstract: Phosphagen kinase systems provide different advantages to tissues with high and fluctuating energy demands, in particular an efficient energy buffering system. In this study we show for the first time functional expression of two phosphagen kinase systems in Saccharomyces cerevisiae, which does not normally contain such systems. First, to establish the creatine kinase system, in addition to overexpressing creatine kinase isoenzymes, we had to install the biosynthesis pathway of creatine by co-overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…The role of the AK in any bacterial species is unknown, but it is tempting to speculate that the addition of an AK gene to a genome can confer a selective advantage immediately. This is supported by work conducted by Sauer and colleagues, who demonstrated that the introduction of an AK gene into both eukaryotic and prokaryotic genomes conferred an increased capacity to withstand environmental stress (3,4,25). This is supported by our work in M. xanthus, and thus it is plausible that the introduction of the AK conferred an enhanced ability to tolerate some forms of environmental stress, such as pH, salt, and osmotic stress.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The role of the AK in any bacterial species is unknown, but it is tempting to speculate that the addition of an AK gene to a genome can confer a selective advantage immediately. This is supported by work conducted by Sauer and colleagues, who demonstrated that the introduction of an AK gene into both eukaryotic and prokaryotic genomes conferred an increased capacity to withstand environmental stress (3,4,25). This is supported by our work in M. xanthus, and thus it is plausible that the introduction of the AK conferred an enhanced ability to tolerate some forms of environmental stress, such as pH, salt, and osmotic stress.…”
Section: Discussionsupporting
confidence: 79%
“…Phosphagen kinases have been shown to have protective effects against a variety of stressors in many organisms and could potentially affect vegetative growth of M. xanthus under stress conditions, including salt, osmotic, pH, and oxidative stress (3,4,25). To determine if M. xanthus ark plays a role in the response to any of these stressors, we constructed an in-frame deletion that Numbering is relative to that of the rabbit muscle CK (RmCK) sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies were conducted at a single ATP concentration (0.5 mM) that is below the typical cytoplasmic ATP concentration measured in yeast cells (44). In addition, it had previously been reported for the V-ATPase from bovine brain clathrin-coated vesicles that the tightness of coupling of proton transport and ATPase activity by the V-ATPase varied as a function of ATP concentration, with higher concentrations of ATP leading to a progressive uncoupling of these activities (42).…”
Section: Atp Dependence Of the Coupling Efficiency Of Proton Transpormentioning
confidence: 99%
“…AK plays an important role as a regulator of energetic reserves and cell growth by catalyzing the reversible transfer of the phosphate group from MgATP to arginine, leading to production of phosphoarginine and MgADP [29] . Canonaco et al [30] reported that recombinant yeast expressing AK showed improved resistance under stress challenges that drain cellular energy, which were transient pH reduction and starvation. Probably the increase in the level of AK in the resistant insects is required to replenish the energy in the resistant larval midgut cells that have a relatively higher utilization to adjust to the extreme conditions than the susceptible strain.…”
Section: Discussionmentioning
confidence: 99%